2008
DOI: 10.1002/tox.20375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2,4‐dichlorophenol on the expression of vitellogenin and estrogen receptor genes and physiology impairments in Chinese rare minnow (Gobiocypris rarus)

Abstract: 2,4-Dichlorophenol (2,4-DCP) is known as a toxicant, but unknown as an environmental endocrine disruptor. In the present work, Chinese rare minnow (Gobiocypris rarus) was exposed to 0.03, 0.3, and 3 mg/L 2,4-DCP for 3 d and 0.1, 0.3, and 1 mg/L 2,4-DCP for 21 d, respectively. Endpoints including somatic index, vitellogenin (VTG) mRNA and protein level, estrogen receptor (ER) mRNA and histopathology were measured. In the 3-d exposure experiment, the effect concentrations were 0.3 mg/L and above, and in 21-d exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 30 publications
(34 reference statements)
5
36
1
Order By: Relevance
“…Nevertheless, cellular vacuolization, hepatocyte hypertrophy and nuclear pyknosis were observed in the liver of the rare minnows, which confirmed the hepatotoxicity induced by DCNP. Similar types of histological damage have been observed in fish exposed to several substituted phenols such as nonylphenol, nitrophenol and DCP (Lam et al, 2013;Zhang et al, 2008). Additionally, DCNP has been shown to induce oocyte and testis degeneration in this study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Nevertheless, cellular vacuolization, hepatocyte hypertrophy and nuclear pyknosis were observed in the liver of the rare minnows, which confirmed the hepatotoxicity induced by DCNP. Similar types of histological damage have been observed in fish exposed to several substituted phenols such as nonylphenol, nitrophenol and DCP (Lam et al, 2013;Zhang et al, 2008). Additionally, DCNP has been shown to induce oocyte and testis degeneration in this study.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the plasma VTG level increased in male fish after DCNP exposure, which confirmed that DCNP was acting as a xenoestrogen. It has been reported that substituted phenols such as 2.4-DCP induce the synthesis of VTG in many fish species (Zhang et al, 2008). However, a slight decrease in female fish at a concentration of 200 mg/L occurred in this study, suggesting weak estrogenic activity of DCNP in female fish.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Triclosan (TCS), benzophenone-3 (BP-3) (a u.v.-filter) and several other phenols also appear to have endocrine-disrupting activity with adverse effects on, e.g. thyroid and reproductive function (Zhang et al 2008, Li et al 2010, Rodriguez & Sanchez 2010, Jung et al 2012, Krause et al 2012, Henry & Fair 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Rare minnow (Gobiocypris rarus), which is mainly distributed in upstream of the Yangtze River, has been selected as an appropriate native species for risk assessment by Chinese government due to its small size, ease of culture and sensitivity to chemical exposure (Zha et al, 2007(Zha et al, , 2008Zhang et al, 2008b). In vivo models for evaluating the disruptions on HPG/I axis was developed using Chinese rare minnow, and have been validated useful for studying endocrinedisrupting effects and the underlying molecular mechanisms (Zhang et al, 2008a;Yang et al, 2010Yang et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%